Key Determinants of Using Derivatives in the UK - Guo, Di (2007)
There is a rather limited but growing use of derivatives for risk management currently. Modern financial theories predict some characteristics of firms that drive their decisions of use derivatives. In this dissertation, empirical evidence on determinants of derivative financial instruments usage is provided with a large sample of the UK's non-financial firms. FTSE 100 and FTSE 250 are chosen to be the initial sample of this study. Different results are reported in the adoption and intensity tests. Based on evidence, the author draws the following conclusions. Both tax incentive and liquidity level are shown to drive the decision of whether firms use derivatives and the extent to which they use these financial instruments. Moreover, the probability of using derivatives is positively associated with leverage level and firm value; while the level of using derivatives is positive correlated with managerial shareholdings, managerial option ownership, and dividend payout. The findings in this study are generally consistent with extant theories except that managerial option ownership is positive rather negative determinant of the level of use derivatives.